Business strategy design methodologies: from product design to platform design - E. V. Vasilieva (Управление)
The article presents an analysis of modern methodologies that are successfully used for the development of innovative products and ecosystem platforms. The paper describes the tools of the “Jobs To Be Done” approach. The author highlights the differences between the two concepts “Jobs-As-Activities” and “Jobs-As-Progress”. The study emphasizes the importance of studying the digital client path. The publication presents by step-by-step an algorithm for constructing a strategy for bringing a new offer to the market based on the “Jobs To Be Done” method. The article presents examples of filling in the Job stories Canvas, interview framework in “Jobs To Be Done” format, Process Making Forces Canvas.The study shows the tools that are successfully used in creating a business strategy based on an ecosystem platform. The paper substantiates the importance of customer-oriented approach and switching to an ecosystem approach to the development of a business model. The author highlights the benefits from the ecosystem of the user, business owner and partners.The study gives an overview of ecosystem types according to the Gartner classification with examples in Russian ecosystems. The author provides tools of the Platform Design (Platform Innovation Kit) which allow you to develop an integrated environment for the development of the customer experience, to improve consumer goods and services: VRIO framework, a Matrix of Motivation, the Ecosystem Platform Relations Canvas, Training Mechanism Canvas, Value Proposition Canvas and Platform Business Models Canvas. These tools expand the design thinking portfolio.